Stereoselective synthesis of highly substituted tetrahydrofurans by diverted carbene O–H insertion reaction - Nicolle, Simon M.; Lewis, William; Hayes, Christopher J.; Moody, Christopher J. (Wiley-VCH Verlag, 2015)
Copper or rhodium catalyzed reaction of diazocarbonyl compounds with β-hydroxyketones gives highly substituted tetrahydrofurans with excellent diastereoselectivity, under mild conditions, in a single step process that starts as a carbene O–H insertion reaction but is diverted by an intramolecular aldol reaction.